Aspek Pendidikan dalam Al-Qur’an: Interpretasi terhadap Ayat-ayat Pendidikan pada Al-Qur’an Surah Al-A’raf ayat 73-79 - Wisnawati Loeis (Turats, 2009)
This article describes about the aspect of education in the Holy Qur’an especially in the Surah al-A’raf verses 73-79. This article is interpretation of that verses and also explains on munasabah (relation) of the verses, structure of language, and the implication of education. From this article we know that Surah al-A’raf verses 73-79 have some meaning of education for us such as teaching of tauhid and anti-paganism, motivation to learn of knowledge and ethical life.